Evaluation of knowledge and awareness of medical students about the relationship between the periodontal diseases and diabetes mellitus - Hocaoğulları, Susan Vanjıku (My University, 2019)
Amaç: Bu çalışmanın amacı tıp öğrencilerinin periodontal hastalıklar (P.H.) ile diyabetes mellitüs (D.M.) arasındaki ilişki üzerine bilgi ve farkındalıklarını değerlendirmekti.Gereç ve Yöntem: Marmara Üniversitesi’nde 5. sınıflardan 135 (%49,8) ve 6. sınıflardan 136 (%50,2) tıp öğrencisinde 34 sorudan oluşan bir anketle kesitsel bir çalışma gerçekleştirildi.Bulgular: Katılımcılardan %80’inden fazlası periodontal sağlığın genel sağlık için önemli olduğunun ve diş ipi kullanımı ve fırçalama alışkanlıklarının bunu sağlamamızdaki öneminin farkındaydılar. Katılımcıların sadece %43’ü D.M. ve P.H. arasındaki ilişkiden haberdardı ve %27’si ise bu ilişki hakkındaki çalışmalar üzerine bilgi sahibiydi. Öğrencilerden sadece %50’si D.M.’nin kontrolünde P.H.’nin önemini kabul ediyordu. Yaklaşık %93’ü, P.H. riskinin düşürülmesi için, tıp doktorları ve diş hekimleri arasındaki iş birliğinin gerekli olduğuna inanıyordu. Katılımcaların yaklaşık %75 ise P.H. nin D.M. üzerine etkileri konusunda ek bilgi almayı arzu ediyordu.Sonuçlar: D.M.’li hastalara yarar sağlamak adına dental-medikal işbirliği, medikal öğrencilerin eğitim programlarına ağız hijyeni, P.D.’nin önemi ve bunun D.M. ile olan ilişkisine yönelik derslerin müfredata eklenmesiyle geliştirilmelidir.

The purpose of the study was to evaluate the knowledge and awareness of medical students about the relationship between periodontal diseases (P.D.) and diabetes mellitus (D.M.).Materials and Methods: A cross-sectional study was conducted on 135 (49,8%) of 5th grade and 136 (50,2%) of 6th grade medical students of Marmara University using a questionnaire that contained 34 questions.Results: Of the respondents, more than 80% were conscious that good periodontal health was important for our overall health and that tooth brushing and flossing were important habits to accomplish. Only 43% of the respondants were familiar about the association between D.M. and P.D. and 27% had knowledge about the studies that showed this link. Only 54% of students agreed that P.D. was an important issue in controlling D.M. About 93% of them believed that collaboration between physicians and dental professions is required to reduce the risk of P.D. About 75% of the participants desired to obtain additional information about P.D. and its impact on D.M.Conclusion: The dental-medical collaboration should be improved for the benefit of the D.M. patients, by integrating the courses on oral hygiene, importance of P.D. and it’s relation to D.M. in the medical students educational curriculum.
Keywords: Awareness; Bilgi; Diabetes mellitus; Diyabetes Mellitüs; Farkındalık; Knowledge; Periodontal disease; Periodontal hastalık